New York City English - Newman, Michael (Dialects of English, 2014)
New York City English is one of the most recognizable of US dialects, and research on it launched modern sociolinguistics. Yet the city's speech has never before received a comprehensive description and analysis. In this book, Michael Newman examines the differences and similarities among the ways English is spoken by the extraordinarily diverse population living in the NY dialect region. He uses data from a variety of sources including older dialectological accounts, classic and recent variationist studies, and original research on speakers from around the dialect region. All levels of language are explored including phonology, morphosyntax, lexicon, and discourse along with a history of English in the region. But this book provides far more than a dialectological and historical inventory of linguistic features. The forms used by different groups of New Yorkers are discussed in terms of their complex social meanings. Furthermore, Newman illustrates the varied forms of sociolinguistic significance with examples from the personal experiences of a variety of New Yorkers and includes links to sound files on the publisher's site and videos on YouTube. The result is a rigorous but accessible and compelling account of the English spoken in this great city.